Pengembangan Potensi Desa Sukoreno Terhadap Produk Makanan Tempe Besengek Melalui Pemasaran Digital Facebook - Quita, Agnes Gracia (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Sukoreno village, Sentolo District of Kulon Progo Recency, have a great potential both in the form of tourism derived from natural attraction, also from its handicrafts, and its regional delicacy specialties. To support Sukoreno village maximizing its potential resources, we need develop marketing strategy through branding program. The approach of digital marketing that we’ve propose on our suggestion is Facebook Ads. With Facebook there are possibilities to promote Sukoreno Village. One mechanism that we can approach is implementing advertising (in Facebook) to promote Tempe Besengek, which known as a traditional dish of Kulon Progo, and how this product is different from the usual tempe in other places. The branding program through Facebook Ads hopefully will increase the regional revenue and expected to boost the image of Sukoreno village to become countryside tourist destination